The Role of Transient Receptor Potential A1 and G Protein-Coupled Receptor 39 in Zinc-Mediated Acute and Chronic Itch in Mice - Hu, Yue; Fu, Qing-Yue; Fu, Dan-Ni; Wang, Xue-Long; Wang, Zhi-Hong; Zhang, Jiang-Tao; Xu, Wen-Jing; Zhou, Guo-Kun; Chen, Li-Hua; Liu, Tong (Frontiers in Molecular Neuroscience, 2022)
Itching is a common symptom of many skin or systemic diseases and has a negative impact on the quality of life. Zinc, one of the most important trace elements in an organism, plays an important role in the regulation of pain. Whether and how zinc regulates itching is largely unclear. Herein, we explored the role of Zn2+ in the regulation of acute and chronic itch in mice. It is found that intradermal injection (i.d.) of Zn2+ dose-dependently induced acute itch and transient receptor potential A1 (TRPA1) participated in Zn2+-induced acute itch in mice. Moreover, the pharmacological analysis showed the involvement of histamine, mast cells, opioid receptors, and capsaicin-sensitive C-fibers in Zn2+-induced acute itch in mice. Systemic administration of Zn2+ chelators, such as N,N,N′,N′-Tetrakis(2-pyridylmethyl)ethylenediamine (TPEN), pyrithione, and clioquinol were able to attenuate both acute itch and dry skin-induced chronic itch in mice. Quantitative polymerase chain reaction (Q-PCR) analysis showed that the messenger RNA (mRNA) expression levels of zinc transporters (ZIPs and ZnTs) significantly changed in the dorsal root ganglia (DRG) under dry skin-induced chronic itch condition in mice. Activation of extracellular signal-regulated kinase (ERK) pathway was induced in the DRG and skin by the administration of zinc or under dry skin condition, which was inhibited by systemic administration of Zn2+ chelators. Finally, we found that the expression of GPR39 (a zinc-sensing GPCR) was significantly upregulated in the dry skin mice model and involved in the pathogenesis of chronic itch. Together, these results indicated that the TRPA1/GPR39/ERK axis mediated the zinc-induced itch and, thus, targeting zinc signaling may be a promising strategy for anti-itch therapy.